Legal Protections for Truck Driver Employment Contracts According to Legislative Regulations - Fatriani, Fenny; Nelina, Naswa (Jurnal Penelitian Ilmiah INTAJ, 2025)
Legal protection for employment contracts for truck drivers is a crucial element in safeguarding the rights of workers within the transportation sector. This article examines the challenges and opportunities associated with the implementation of employment agreements in accordance with relevant legislation, including Law No. 13 of 2003 on Manpower.  The findings reveal that a significant number of truck drivers operate without written employment agreements, which exposes them to various rights violations, such as inadequate wages, insufficient social security, and excessive working hours. Furthermore, existing protections for occupational safety and compensation in the event of accidents are notably lacking. This study recommends policy enhancements that include the requirement for companies to establish written employment contracts, register employees with the Employment Social Security Agency (BPJS Ketenagakerjaan), and ensure equitable wages and working conditions. Adopting these measures is expected to foster a more just and productive working relationship for truck drivers.